Temporary international mobility, Family Timing, Dual Career and family democracy. A case of Swedish medical professionals - Wolanik Boström, Katarzyna; Öhlander, Magnus; Pettersson, Helena (Migration Letters, 2018)
The article, based on 43 narrative interviews with Swedish physicians and molecular biologists, discusses family timing and family management as crucial factors in temporary international mobility of highly skilled professionals. In the narratives, the family often created a kind of inertia and complication for a prolonged period of working abroad. The interviewees’ dreams and wishes had to be negotiated with a partner pursuing his/her own career, as well as the rest of the family, and there were also a lot of logistics and practicalities to take care of. However, mobility was also regarded as an amazing opportunity for the whole family to be together and to learn about new cultural and social contexts. In several narratives, the temporary and thus “parenthetic” living abroad influenced the otherwise cherished ideals of dual careers, equal gender contract and a respectful parenthood.